Parametric finite element contour mapping - Berry, K.J. (Computers & structures, 1990)
A complete bi-quadratic parametric function is used to map nodal resultants, and geometry, over the finite element parametric space. These parametric functions are then used to determine contour lines representing the element resultants. The source code for the C-base algorithm is provided and is applicable to 2-D and 3-D linear and quadratic elements. The algorithm can also be applied to any 3-D surface limited to nine total degrees of freedom in any one spatial dimension.